Action-Based Help Technique To Improve Learnability And Understandability Of Web Applications - Shamsuddin, Nurul Afiqah (2014)
The emergence of the Internet has created a tremendous demand for Web applications. Acceptability of Web applications is heavily dependent on its usability factor. A Web application is one of the platforms where users often experience frustration. This frustration accumulates once they encounter difficulties to learn and understand the functions after discovering the functions earlier. Learnability and understandability are two crucial factors of usability. Thus, it is a challenge for Web developers and designers to ensure that Web applications will continuously support users’ understanding and learning processes. This research focuses on improving the learnability and understandability of Web applications through an Action-Based Help (ABH) technique. The proposed technique has been designed to capture users’ interactions on a Graphical User Interface (GUI) in order to determine which of the functions that users require guidance. This technique also provides guidance through a help system that uses video demonstration and tooltip technology to enhance users understanding towards the functionality. A controlled experiment has been conducted to evaluate its effectiveness in enhancing users’ understanding towards Web functionalities. It was discovered that through the adoption of the proposed technique, users are able to understand the functions better compared to the textbased online help. Users also able to complete tasks given in shorter time and obtained lower frequency in help accesses compared with text-based online help.